The Role of Indonesian Muslim Millennials in Reducing Food Waste towards Sustainable Development Goals: Empirical Analysis PLS-SEM - Alfarizi, Muhammad (JAWAB: Journal of Asian World and Islamic Behavior Journal of Asian World and Islamic Behavior, 2024)
Food waste is a critical concern under SDGs 12 due to its global welfare implications. Islam, with its substantial following worldwide, can play a role in addressing this issue, particularly through the involvement of Muslim millennials. This study aims to explore the impact of religiosity, product usage efficiency, and intention to reduce food waste, with da’wah, Instagram, and Muslim eating manners as mediators. Quantitative research was conducted through an online survey of Indonesian millennials using purposive sampling. The research model, consisting of five hypotheses, was analyzed using the PLS-SEM analysis method. Results indicate that individual religiosity significantly influences Instagram proselytizing and eating behavior among Muslim millennials. Instagram proselytizing strongly affects millennial Muslim consumer behavior, particularly in terms of food consumption efficiency. Additionally, Muslim millennials’ eating etiquette impacts food consumption efficiency and environmental awareness. The efficiency of food consumption can shape millennials’ intention to reduce food waste. Implications of this study include promoting millennial involvement in food waste reduction, sustainable agricultural practices, improving literacy on food consumption efficiency, incorporating food waste education in Islamic religious curricula, and fostering collaboration among Muslim millennial organizations in Indonesia’s food waste reduction programs.